2017
DOI: 10.1186/s13098-017-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Muscle irisin response to aerobic vs HIIT in overweight female adolescents

Abstract: BackgroundExercise stimulates the production of fibronectin type III domain-containing protein 5 (FNDC5), which is cleaved to release a protein called irisin. This protein induces browning of white adipose tissue resulting in increased thermogenesis. Different studies have measured circulating irisin at baseline and in response to exercise among a wide variety of individuals; yet, regarding the effect of different exercise intensities in obese adolescent girls, limited insight is available. This study compares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 42 publications
1
29
0
2
Order By: Relevance
“…As such, high-intensity interventions in sedentary subjects have induced a greater increase in irisin levels than low-intensity exercise with a similar energy consumption [38]. It should also be noted that although Archundia-Herra et al found significant increases in the levels of muscle irisin, the level of plasma irisin remained unchanged 30 min after HIT [2]. To properly interpret the data on acute irisin responses, the point of time when the blood samples were taken has also to be considered, as the level of irisin is reported to return to the baseline value within 15 min after a HIT session [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, high-intensity interventions in sedentary subjects have induced a greater increase in irisin levels than low-intensity exercise with a similar energy consumption [38]. It should also be noted that although Archundia-Herra et al found significant increases in the levels of muscle irisin, the level of plasma irisin remained unchanged 30 min after HIT [2]. To properly interpret the data on acute irisin responses, the point of time when the blood samples were taken has also to be considered, as the level of irisin is reported to return to the baseline value within 15 min after a HIT session [40].…”
Section: Discussionmentioning
confidence: 99%
“…To properly interpret the data on acute irisin responses, the point of time when the blood samples were taken has also to be considered, as the level of irisin is reported to return to the baseline value within 15 min after a HIT session [40]. In addition, exercise-induced increases in muscle irisin have been shown to be much higher than those in plasma, suggesting that the physical strain was too low (6 bouts of 1 min at 85-95 % HR peak ) to cause changes in the plasma irisin levels [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that single exercise interventions consisting of 45-60 min ergometer cycling [102,153] or treadmill tests to volitional failure [155] can increase circulating irisin. However, reductions in plasma irisin have also been observed after shortterm moderate intensity training [156] and after interval training [157]. Many studies have also reported no change in circulating irisin after acute exercise bouts under 60 min [156,[158][159][160].…”
Section: (▶ Table 3)mentioning
confidence: 99%
“…However, reductions in plasma irisin have also been observed after shortterm moderate intensity training [156] and after interval training [157]. Many studies have also reported no change in circulating irisin after acute exercise bouts under 60 min [156,[158][159][160]. These conflicting results extend to chronic exercise exposure.…”
Section: (▶ Table 3)mentioning
confidence: 99%